The Effect of Workload and Work Stress on Bank Employees Performance in North Kolaka Regency - Sasmita (Scientia integritas Utama, 2023)
Humans as the driving force of the company is the main factor as the existence of the company depends on the people involved behind it. The company's achievements cannot be separated from the good performance of each of its employees. Employees who have good performance will encourage the company to achieve its goals well too. Conversely, employees with poor performance will affect the stability of the company. Some of the factors that can affect performance include the level of workload given by the company to its employees and the job satisfaction felt by employees towards their work. This study aims to analyze the effect of workload and job satisfaction on employee satisfaction. The research method uses a cross-sectional study design. The research began in April-May 2023 at a bank in North Kolaka Regency. The number of samples used was 82 respondents obtained from the Slovin formula and selected using accidental sampling technique. Data collection was measured using a questionnaire with a Likert scale which was filled in directly by the respondents. Data were analyzed using the Chi-Square test and Multiple Logistic Regression test. The test results show that there is an influence of workload and job satisfaction on bank employee satisfaction in North Kolaka Regency. The company should pay attention to the suitability of the responsibilities given to employees and always meet the needs of employees so that they can produce good performance and in accordance with company goals. The number of samples used was 82 respondents obtained from the Slovin formula and selected using accidental sampling technique. Data collection was measured using a questionnaire with a Likert scale which was filled in directly by the respondents. Data were analyzed using the Chi-Square test and Multiple Logistic Regression test. The test results show that there is an influence of workload and job satisfaction on bank employee satisfaction in North Kolaka Regency. The company should pay attention to the suitability of the responsibilities given to employees and always meet the needs of employees so that they can produce good performance and in accordance with company goals. The number of samples used was 82 respondents obtained from the Slovin formula and selected using accidental sampling technique. Data collection was measured using a questionnaire with a Likert scale which was filled in directly by the respondents. Data were analyzed using the Chi-Square test and Multiple Logistic Regression test. The test results show that there is an influence of workload and job satisfaction on bank employee satisfaction in North Kolaka Regency. The company should pay attention to the suitability of the responsibilities given to employees and always meet the needs of employees so that they can produce good performance and in accordance with company goals.